Boron application in the production and quality of cauliflower seeds (Research, Society and Development, 2020)
Studies on the effect of foliar fertilization on the production and quality of vegetable seeds are still scarce. There is a lack of information regarding recommendations that provide an increase in the production of seeds with high physiological potential. Thus, the objective was to evaluate the effect of boron application via leaf at different phenological stages of cauliflower on the production and phenological quality of seeds. The experiment was carried out from January 2017 to March 2018. The studied species was the cauliflower cultivar Piracicaba Precoce with 16 treatments, resulting from the combination of number of applications (1, 2, 3, 4, 5) of boron leaf pathway at 1.0 g L-¹ in five phenological stages: 30 cm floral stem; opening of the first flowers; formation of the first silicas; 50% of silica formed and 100% of silica formed, in addition to control without application of boron. The experimental design was in randomized blocks with four replications. According to the results, it was observed that the application of boron via leaf at different phenological stages of 'Piracicaba Precoce' cauliflower did not differ from the control (without boron) for seed production. Perform an application of boron via leaf to produce cauliflower seeds in the stages: opening of the first flowers (average: 96%); in the formation of the first silicas (average: 94%), and at the moment when there are 100% of silicas formed (still green) (average: 93%), there is an increase in vigor on average of 16% more when compared to plants with 30 cm of floral stem (younger stage, average: 78% vigor).